2003
DOI: 10.1245/aso.2003.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Chemohyperthermia Using a Closed Abdominal Procedure and Cytoreductive Surgery for the Treatment of Peritoneal Carcinomatosis: Morbidity and Mortality Analysis of 216 Consecutive Procedures

Abstract: The frequency of complications after IPCH and cytoreductive surgery was mainly associated with the carcinomatosis stage and the extent of the surgical procedure. The IPCH closed abdominal procedure has shown an acceptable frequency of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
195
4
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(224 citation statements)
references
References 16 publications
15
195
4
10
Order By: Relevance
“…The combination of hyperthermia and high concentration chemotherapy used in HIPEC can also alter physiological healing, which may increase the incidence of anastomotic leaks and GI complication rates [13]. Among the larger series [13][14][15][16][17][18], the reported grade III/IV GI complication rate ranges between 4.5 to 19 %. Small bowel perforations and anastomotic leaks are the most common and clinically significant GI complications after CRS and HIPEC.…”
Section: Gastrointestinal (Gi) Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of hyperthermia and high concentration chemotherapy used in HIPEC can also alter physiological healing, which may increase the incidence of anastomotic leaks and GI complication rates [13]. Among the larger series [13][14][15][16][17][18], the reported grade III/IV GI complication rate ranges between 4.5 to 19 %. Small bowel perforations and anastomotic leaks are the most common and clinically significant GI complications after CRS and HIPEC.…”
Section: Gastrointestinal (Gi) Complicationsmentioning
confidence: 99%
“…Patients undergoing peritonectomy procedures have a significant risk of post-operative infectious complications and pneumonia is approximately reported in 3.2-10 % of patients [14,15,[24][25][26][27][28][29]. Several studies showed that pulmonary complications can be reduced by local experience, better peri-operative fluid and glycemic control and multi-disciplinary management of patients undergoing CRS and HIPEC [9,[30][31][32].…”
Section: Pulmonary Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been no increased risk of anastomotic recurrence or gastrointestinal fistula reported by centres that perform the closure prior to HIPEC [46]. The major advantage of the closed technique is the ability to rapidly achieve and maintain hyperthermia, as there is minimal heat loss from a closed abdomen.…”
Section: Perfusion Techniquesmentioning
confidence: 99%
“…Similarly, non-anatomic liver resection may be required in patients with extensive deposits on the liver surface. In patients with ovarian cancer, synchronous resection of intraparenchymal liver metastases can be performed with CRS, especially in patients with solitary liver metastases [76,77].…”
Section: Colectomy Distal Pancreatectomy Hepatic Resectionmentioning
confidence: 99%